Vooraan vlnr.: Van Dam, Van der Stoel, Schaefer; 2e rij: links: Liesbeth en Joop den Uyl - Dijkstra, Ger, (1975)
Vooraan vlnr.: Van Dam, Van der Stoel, Schaefer; 2e rij: links: Liesbeth en Joop den Uyl.